Moments of Magical Realism in US Ethnic Literatures
X, 279 p. 1 illus.
Keywords: A collection of essays that explores magical realism as a momentary interruption of realism in US ethnic literature, showing how these moments of magic realism serve to memorialize, address, and redress traumatic ethnic histories.